Breastfeeding practices among mothers attending a tertiary care hospital in Kashmir - Ain, Syed Najmul; Qulsum, Reyana; Rizwan, Amtul (International Journal Of Community Medicine And Public Health, 2023)
Background: According to world health organization (WHO), exclusive breastfeeding (EBF) for the first 6 months of life is vital for optimal growth and development of a child. During this period, other liquids or breastfeeding substitutes should not be given to infants except for medicine or oral rehydration solution. Methods: This cross-sectional study was conducted in the child health clinic of the department of community medicine, SKIMS. The study participants were mothers accompanying their infants coming for immunisation at the child health centre. A semi-structured, questionnaire was used to interview the mothers regarding breast feeding practices of their infants. The data was entered in Microsoft excel 2010 and analysed using SPSS Version 20. Results: The prevalence of EBF was 38.7%. Mixed feeding was received by 54% and 7.3% were formula-fed. Variables that were significantly associated with EBF include residence and mother’s education. Infants from rural area were more likely to be exclusively breastfed compared to those from urban area (OR=0.365; 95% CI=0.166-0.802; p=0.012). Mothers with up to 9 years of formal education were more likely to exclusively breastfed their children than those with more than 9 years of formal education (OR=0.300;95% CI=0.121-0.744, p=0.009). Conclusions: To ensure that the rate of EBF among the mothers is increased, all the stakeholders (spouse, family and government) as well as the people at work place must play their part to the best extent.